Factors associated with the prevalence of antibodies against Theileria equi in equids of Western Pará, Brazil - Minervino, Antonio Humberto Hamad; Torres, Allana Cavalcante; Moreira, Thiago Rocha; Vinholte, Brena Peleja; Sampaio, Bruna Matarucco; Bianchi, Daniela; Portela, Juliana Machado; Sarturi, Cristiane; Marcili, Arlei; Barrêto Júnior, Raimundo Alvês; Gennari, Solange Maria; Machado, Rosangela Zacarias [UNESP] (Hindawi, 2019)
The State of Pará has one of the largest herds of equids (horse, donkey and mule) in Brazil, most of these animals are found on cattle farms. Equine theileriosis is a tick-borne disease caused by the parasite Theileria equi and is characterized by fever, anaemia, icterus, intravascular haemolysis, haemoglobinuria, spleen and hepatomegaly, and even death. The present study aimed to determine the prevalence of antibodies against T. equi in equids in the western region of the State of Pará, Brazil, and to identify potential risk factors associated with parasite infection. A cross-sectional study was conducted with cluster sampling of farm horses from 18 municipalities. In the cities visited, samples from sport and carthorses were also included. Serum was obtained to detect T. equi-specific antibodies using an indirect enzyme-linked immunosorbent assay (iELISA) based on a crude parasite antigen. In order to identify possible risk factors of the infection which are associated with the prevalence of antibodies, a chi-squared test was carried out. Of 1,117 equids, 373 tested positive for T. equi antibodies with an overall prevalence of 33.4% (31.3%–37.0% for the 95% confidence interval). Sex, animal species and breed were found not to be associated with the presence of T. equi antibodies, whereas age, the presence of dogs or ticks were associated with seropositivity (p < 0.05). Horses with ticks were 2.4 more likely seropositive than horses without ticks. The presence of dogs in the equid habitat and the presence of ticks resulted in a higher T. equi seropositive rate probably because dogs are hosts for vector ticks of T. equi. Our study represents the first report of T. equi antibodies in equids of western Pará revealing a widespread distribution of seropositive animals.
Keywords: carthorse; ELISA; piroplasmosis; sport horse; survey